Kant and the philosophy of history - Yovel, Yirmiyahu (New Yersey Princeton university press, 1980)
This book grew out of over a decade of intermittent Kant studies. As a young undergraduate in Jerusalem, then under strong Neo-Kantian influece, I was led to think that Kant had spelled the doom of all metaphysics, and that his contribution to ethics lay in his formal, all too formal, doctrine of the categorical imperative. As for his essay on history, if they deserved attention at all, they were to be deemed incompatible with the system.